EFFECT OF DIFFERENT TILLAGE SYSTEM ON SOME SOIL PHYSICAL PROPERTIES AND CROP YIELD OF BARELY (HORDEUM VULGARE) - Talal Jaber Abd Al Khanfous (European Journal of Agricultural and Rural Education, 2024)
The study was conducted at the Station of agricultural Research in the College of Agriculture and Marches, University of Thi- Qar, during the 2017-2018 and 2018-2019 seasons to study the impact of various tillage systems on certain physical properties of soil, yield, and components of barley. The treatments included various tillage systems which are moldboard plow(T1), chisel plow (T2) , moldboard plow with one pass of disc harrows (T3), chisel plow with one pass of disc harrows(T4), moldboard plow with three passes of disc harrow (T5), chisel plow with three passes of disc harrow (T6), and no tillage (T7). These treatments were arranged using a randomized complete block design (R.C.B.D) with three replications. The data were analyzed using the Genstat program, and mean comparisons were performed using the least significant difference (LSD) test. The results indicated a significant effect of tillage systems and year on the parameters studied. The treatment (T3) outperformed the other treatments in enhancing soil physical properties, yield, and components of barley crop.